Trade Creation and Trade Diversion Effects of the ASEAN-China Free Trade Agreement, ASEAN-Korea Free Trade Agreement, and ASEAN-India Free Trade Agreement Implementation on the Export of Indonesia’s Food and Beverages Industry Products - Darma, Wahyudi Setia; Hastiadi, Fithra Faisal (International Journal of Economics and Financial Issues, 2017)
This research is aimed at analyzing the effect of trade creation and trade diversion which occurs on the establishment of such cooperation for the export of Indonesian food and beverage industry products with trading partners either with its members or non-members cooperation. This research is conducted by using a test from 12 countries in the period of 2005-2015 estimated using a modified gravity model by increasing the variable on dummy Free Trade Agreement (FTA) as a proxy from the impact on the implementation of ASEAN-China FTA (ACFTA), ASEAN-Korea FTA (AKFTA), and ASEAN-India FTA (AIFTA). The estimate results of this research suggest that the implementation of ACFTA, AKFTA and AIFTA provides positive and significant effect of trade creation and trade diversion on export of Indonesian food and beverage products. This signifies that the implementation of ACFTA, AKFTA and AIFTA creates a trade creation effect by increasing intra-regional trade between ACFTA, AKFTA and AIFTA member countries and not occur trade diversion with non-member countries. Keywords: Asean-China Free Trade Agreement, Asean-Korea Free Trade Agreement, Asean-India Free Trade Agreement, Trade Creation, Trade Diversion, Gravity Model, Indonesian Food and Beverage Industry Products JEL Classifications: F13; L15